Co-movement revisited: reflections on four decades of media transformation in Canadian Indigenous communities. Issue 3 (3rd April 2018) - Roth, Lorna; Audette-Longo, Patricia H.
ABSTRACT: This viewpoint introduces a long-view assessment of communications developments in northern Canada through a conversation between the authors. Discussing how communications and cultural development practices in Canada's north (north of 60 degrees of latitude) have changed in the last four decades, we advocate relationship-building and co-movement in the development of communities' cultural persistence.